MEPIRAPIM-derived synthetic cannabinoids inhibit T-type calcium channels with divergent effects on seizures in rodent models of epilepsy - Harman, Thomas; Udoh, Michael; McElroy, Dan L.; Anderson, Lyndsey L.; Kevin, Richard C.; Banister, Samuel D.; Ametovski, Adam; Markham, Jack; Bladen, Chris; Doohan, Peter T.; Greba, Quentin; Laprairie, Robert B.; et al. (Frontiers in Physiology, 2023)
Background: T-type Ca2+ channels (Cav3) represent emerging therapeutic targets for a range of neurological disorders, including epilepsy and pain. To aid the development and optimisation of new therapeutics, there is a need to identify novel chemical entities which act at these ion channels. A number of synthetic cannabinoid receptor agonists (SCRAs) have been found to exhibit activity at T-type channels, suggesting that cannabinoids may provide convenient chemical scaffolds on which to design novel Cav3 inhibitors. However, activity at cannabinoid type 1 (CB1) receptors can be problematic because of central and peripheral toxicities associated with potent SCRAs. The putative SCRA MEPIRAPIM and its analogues were recently identified as Cav3 inhibitors with only minimal activity at CB1 receptors, opening the possibility that this scaffold may be exploited to develop novel selective Cav3 inhibitors. Here we present the pharmacological characterisation of SB2193 and SB2193F, two novel Cav3 inhibitors derived from MEPIRAPIM. Methods: The potency of SB2193 and SB2193F was evaluated in vitro using a fluorometric Ca2+ flux assay and confirmed using whole-cell patch-clamp electrophysiology, with in silico docking to the cryo-EM structure of Cav3.1 performed to elucidate structural insights into T-type channel inhibition. Next, in vivo pharmacokinetic parameters in mouse brain and plasma were determined using liquid chromatography-mass spectroscopy. Finally, anticonvulsant activity was assayed in established genetic and electrically-induced rodent seizure models. Results: Both MEPIRAPIM derivatives produced potent inhibition of Cav3 channels and were brain penetrant, with SB2193 exhibiting a brain/plasma ratio of 2.7. SB2193 was further examined in mouse seizure models where it acutely protected against 6 Hz-induced seizures. However, SB2193 did not reduce spontaneous seizures in the Scn1a+/- mouse model of Dravet syndrome, nor absence seizures in the Genetic Absence Epilepsy Rat from Strasbourg (GAERS). Surprisingly, SB2193 appeared to increase the incidence and duration of spike-and-wave discharges in GAERS animals over a four-hour recording period. Conclusion: These results provide proof of principle that MEPIRAPIM analogues provide novel chemical scaffolds to advance Cav3 inhibitors against certain seizure types.